2021
DOI: 10.1128/mbio.02385-21
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Roles for Ribonucleases in Streptococcus pneumoniae Pathogenesis

Abstract: Streptococcus pneumoniae is a notorious human pathogen that adapts to conditions in distinct host tissues and responds to host cell interactions by adjusting gene expression. RNases are key players that modulate gene expression by mediating the turnover of regulatory and protein-coding transcripts.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…RNase Y and PNPase were recently shown to affect S. pneumoniae virulence in a murine model [4]. The transcriptional landscape of the respective mutants indicated a global effect of RNase Y on pneumococcal physiology and an implication of PNPase on S. pneumoniae virulence control, likely through sRNA regulation [4]. In agreement with this, PNPase was shown to interact with several noncoding RNAs in a RNA-protein complexome study [5].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…RNase Y and PNPase were recently shown to affect S. pneumoniae virulence in a murine model [4]. The transcriptional landscape of the respective mutants indicated a global effect of RNase Y on pneumococcal physiology and an implication of PNPase on S. pneumoniae virulence control, likely through sRNA regulation [4]. In agreement with this, PNPase was shown to interact with several noncoding RNAs in a RNA-protein complexome study [5].…”
Section: Introductionmentioning
confidence: 72%
“…In spite of their great importance, not much is known about pneumococcal ribonucleases. RNase Y and PNPase were recently shown to affect S. pneumoniae virulence in a murine model [4]. The transcriptional landscape of the respective mutants indicated a global effect of RNase Y on pneumococcal physiology and an implication of PNPase on S. pneumoniae virulence control, likely through sRNA regulation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Metal amounts in samples were normalized relative to total protein amounts in the matched samples. Mouse models of infection: All procedures were approved in advance by UTHealth Animal Welfare Committee and carried out as previously described (41). Male ICR mice (21-24 g; Envigo) were anaesthetized by inhaling 4 to 5 % isoflurane.…”
Section: Methodsmentioning
confidence: 99%
“…Despite their important roles, knowledge on pneumococcal RNases is still in its infancy, with only a small number of recent studies. RNase R, PNPase and RNase Y were all shown to affect S. pneumoniae virulence [4, 5]. PNPase seems to act on virulence through its interaction with noncoding RNAs [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…RNase R, PNPase and RNase Y were all shown to affect S. pneumoniae virulence [4, 5]. PNPase seems to act on virulence through its interaction with noncoding RNAs [5, 6]. In a recent study RNase YhaM was identified as a stabilizer of noncoding RNAs involved in pneumococcal competence [6].…”
Section: Introductionmentioning
confidence: 99%